Pengaruh Penerapan Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMPN 1 2X11 Enam Lingkung - Winda Dwinovita (Departemen Matematika, 2020)
Problem solving skills are very important in the world of education, therefore problem solving skills must be improved. Based on the results of test at SMPN 1 2X11 Enam Lingkung, it can bee seen that students’ problem solving ability is still low. One of model that can be applied to problem solving is Problem Based Learning. This type of research is quasy experiment using static group design. Based on the final test results, it can be seen that students who use the Problem Based Learning model have an average problem solving ability higher than the average problem solving ability using the conventional model. It can be concluded that the student’s mathematical problem solving ability by using the Problem Based Learning model is better than the problem solving ability by using conventional model.Keywords- Mathematical Problem Solving Ability, Conventional Model, Problem Based Learning.